Assessment and evaluation of possible materials for low thermal energy storage system - Dimaano, Maria Natalia Roxas (1995)
The eutectic moisture of Capric Acid and Lauric Acid was assessed to be the most technically feasible materiqal mong the phase change materials noted as possible media, suitable for Philippine low thermal energy storage system. The characteristics of the different combinations of the acids were verified against existing literature with the use of a Differential Scanning Calorimeter. A total of 120 thermal cycles were carried out authenticating the long-term stability, cycleability and reproducibility of the combination. The observed lowest temperature attained by water in 120 thermal cycles for the combination of 63 and 35 by mole % composition of Capric Acid and Lauric Acid, respectively, provided an average of 11.63°C. This showed that the capability of the combination to lower the temperature of water. The material remained physically the same, exhibiting neither volume change nor degradation in the material. However, the energy density in terms of the calculated latent heat of fusion of the material derived from the experiment yielded lower values than established literature values, requiring experimental set-up design improvement.